2007
DOI: 10.1093/ajcn/86.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Sugars and satiety: does the type of sweetener make a difference?

Abstract: There was no evidence that commercial cola beverages sweetened with either sucrose or HFCS have significantly different effects on hunger, satiety, or short-term energy intakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…In our study, the difference in perceived fullness and satisfaction between the skim milk and fruit drink treatments became larger over time (as evidenced by significant time-by-treatment interactions), which suggests that a difference in energy intake may not have been observed had the test meal been provided much sooner than 4 h after the beverages. Furthermore, other studies providing isoenergetic dairy or sugarbased liquid preloads have reported no difference in energy intake at a test meal provided 1 h later (11,12), 2 h later (14,21), or at the same time as the preload (13).…”
Section: Discussionmentioning
confidence: 91%
“…In our study, the difference in perceived fullness and satisfaction between the skim milk and fruit drink treatments became larger over time (as evidenced by significant time-by-treatment interactions), which suggests that a difference in energy intake may not have been observed had the test meal been provided much sooner than 4 h after the beverages. Furthermore, other studies providing isoenergetic dairy or sugarbased liquid preloads have reported no difference in energy intake at a test meal provided 1 h later (11,12), 2 h later (14,21), or at the same time as the preload (13).…”
Section: Discussionmentioning
confidence: 91%
“…77 Another study showed that drinks that were sweetened with either sucrose or HFCS did not have significantly different effects on hunger, satiety or on energy intake at a subsequent lunch. 78 In the absence of long term studies on the effects of HFCS versus sucrose, it seems premature to blame the switch to HFCS as a major contributor to the pathogenesis of obesity or cardiovascular diseases.…”
Section: The Role Of Caffeine In Soft Drinksmentioning
confidence: 99%
“…Unlike fiber, simple sugars provide little satiating effect, which can foster excessive energy intake [16]. However, studies that have examined the differences between the regulatory mechanisms of satiety of various types of fructose-containing sugar such as sucrose, fructose and high fructose corn syrup (HFCS) did not come to conclusive results [17,18]. Researchers assume that these rapidly absorbed carbohydrates may cause a higher glycemic load, which would be associated with greater insulin response and thus an increased risk of fat accumulation [19,20].…”
Section: Added Sugar and Its Potential Hazardsmentioning
confidence: 99%